Suspicion and other feelings about COVID-19 vaccines and mask-wearing among individuals recovering from substance addiction - Connie Hassett-Walker (Public Health in Practice)
Objective: This study presents findings about vaccination willingness or resistance and mask-wearing among individuals recovering from a substance use disorder during the COVID-19 pandemic period. Study design: Content analysis. Method: Fifty individuals were interviewed. Interviews were transcribed verbatim, and then coded using Atlas Ti qualitative analysis software. A content analysis was conducted, eliciting recurring themes and overarching COVID-19 health behavior dimensions for getting (or not) vaccinated and wearing a mask. Results: While most subjects were willing to get vaccinated and wear mask, a small minority were not. Both formal (mandates) and informal (pressure from others) mechanisms played a role in getting participants to mask-up and get vaccinated, even when they did not want to. Concern for others motivated some individuals to both get vaccinated and wear a mask. Fear and ambivalence emerged as emotional themes, as did suspicion particularly among vaccine-refusing subjects. Reasons for not getting vaccinated included lack of trust in the government, as well as the vaccine-development process. Conclusions: The results suggest that many COVID-19 prevention initiatives have gone right in terms of reaching individuals recovering from substance addiction. Public health officials may consider alternative ways of reaching individuals whose frame of reference regarding vaccines, public health, and government outreach is one of suspicion and distrust of facts. Future research should examine sources of health and medical information, and how these contribute to individuals’ vaccination hesitancy.